Attitudes of Physical Education Teachers and Students towards Manifestations of Tolerance - Audronė Dumčienė; Tomas Saulius (Lithuanian Sports University, 2018)
Research background and hypothesis. In academic literature construct of tolerance has not been sufficiently revealed, limits of tolerance are not clear, especially they vary in different cultures. There is a noticeable increase in the number of children from various ethnic groups in Lithuanian schools. Therefore, multidimensional knowledge of various manifestations of tolerance/intolerance is of great importance. Research aim was to reveal attitudes of PE teachers and students towards manifestations of tolerance/intolerance. Research  methods.  In  our  research  questionnaire  was  applied  with  six  groups  of  tolerance  manifestations distinguished altogether with 36 related statements. There were six other statements according to six groups of tolerance  manifestations  for  the  potential  behavior  of  participants.  Validity  of  the  questionnaire  was  examined calculating Cronbach's constant α: for the first part of the questionnaire Cronbach's α  = 0.87, and for the second - α = 0.79. Values of χ 2  and Student's t criterion were calculated. The sample of the research included 243 students of IX-XII classes form regional schools, 129 students of the same age from city schools, 47 physical education teachers from city schools and 38 teachers from regional schools. Research results. We found statistically significant difference (p  < 0.05) between positive attitudes towards tolerance among students from city schools and positive attitudes among students from regional schools. Statistically significant difference between positive attitudes towards tolerance for PE teachers from city schools and positive attitudes for those from regional schools was not found (p > 0.05). However, there were statistically significant differences between positive attitudes towards tolerance of students from city schools and PE teachers from city schools (χ 2  (5) = 37.27; p < 0.05), also between positive attitudes towards tolerance of students from regional schools and PE teachers from regional schools (χ 2  (5) = 37.27; p < 0.05). We found statistically significant difference (t = 3.81; p < 0.05) between tolerance estimators of students and PE teachers from city schools. On the other hand, relevant differences between tolerance estimators of students from city schools and from regional schools, and differences between tolerance estimators of PE teachers from city schools and from regional schools were not found (p > 0.05). Discussion and conclusion: in fact, attitudes towards intolerance, which are incident to the PE teachers from city schools and their colleagues from regional schools, did not differ, but they contrasted with students' attitudes. In cases of intolerance manifestations, students from city schools would be more passive than students from regional schools, but PE teachers from city schools would be more active than their students. Keywords: tolerance, intolerance, social distance.